Zadacha Kuznecov Predely 10-10

Материал из PlusPi
Перейти к: навигация, поиск

Условие задачи

Вычислить предел функции:

<math>\lim_{x\to 0} \frac{\sqrt[3]{27+x}-\sqrt[3]{27-x}}{x+2\sqrt[3]{x^4}}</math>

Решение

<math>\lim_{x\to 0} \frac{\sqrt[3]{27+x}-\sqrt[3]{27-x}}{x+2\sqrt[3]{x^4}} = \left\{\frac{0}{0}\right\} = </math>
<math> = \lim_{x\to 0} \frac{\left(\sqrt[3]{27+x}-\sqrt[3]{27-x}\right)\left(\sqrt[3]{(27+x)^2}+\sqrt[3]{27+x}\sqrt[3]{27-x}+\sqrt[3]{(27-x)^2}\right)}{\left(x+2\sqrt[3]{x^4}\right)\left(\sqrt[3]{(27+x)^2}+\sqrt[3]{27+x}\sqrt[3]{27-x}+\sqrt[3]{(27-x)^2}\right)} = </math>
<math> = \lim_{x\to 0} \frac{27+x-(27-x)}{\left(x+2x\sqrt[3]{x}\right)\left(\sqrt[3]{(27+x)^2}+\sqrt[3]{27+x}\sqrt[3]{27-x}+\sqrt[3]{(27-x)^2}\right)} = </math>
<math> = \lim_{x\to 0} \frac{27+x-27+x}{x\left(1+2\sqrt[3]{x}\right)\left(\sqrt[3]{(27+x)^2}+\sqrt[3]{27+x}\sqrt[3]{27-x}+\sqrt[3]{(27-x)^2}\right)} = </math>
<math> = \lim_{x\to 0} \frac{2x}{x\left(1+2\sqrt[3]{x}\right)\left(\sqrt[3]{(27+x)^2}+\sqrt[3]{27+x}\sqrt[3]{27-x}+\sqrt[3]{(27-x)^2}\right)} = </math>
<math> = \lim_{x\to 0} \frac{2}{\left(1+2\sqrt[3]{x}\right)\left(\sqrt[3]{(27+x)^2}+\sqrt[3]{27+x}\sqrt[3]{27-x}+\sqrt[3]{(27-x)^2}\right)} = </math>
<math> = \frac{2}{\left(1+2\sqrt[3]{0}\right)\left(\sqrt[3]{(27+0)^2}+\sqrt[3]{27+0}\sqrt[3]{27-0}+\sqrt[3]{(27-0)^2}\right)} = </math>
<math> = \frac{2}{1\cdot \left(\sqrt[3]{27^2}+\sqrt[3]{27}\sqrt[3]{27}+\sqrt[3]{27^2}\right)} = \frac{2}{1\cdot \left(3^2+3\cdot 3+3^2\right)} = \frac{2}{27}</math>